2015
DOI: 10.1089/aid.2014.0370
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine Resistance in Previously Nevirapine-Unexposed HIV-1-Infected Kenyan Infants Initiating Early Antiretroviral Therapy

Abstract: Nevirapine (NVP) resistance occurs frequently in infants following NVP use in prevention of mother-to-child transmission (PMTCT) regimens. However, among previously NVP-unexposed infants treated with NVPantiretroviral therapy (ART), the development and impact of NVP resistance have not been well characterized. In a prospective clinical trial providing early ART to HIV-infected infants < 5 months of age in Kenya (OPH03 study), we followed NVP-unexposed infants who initiated NVP-ART for 12 months. Viral loads we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In Mali, baseline NNRTI resistance was common in children without reported PMTCT drug exposure and was associated with increased risk of treatment failure [ 33 ]. Reports from Central African Republic [ 35 ] and Kenya [ 34 ] show drug resistance in as high as 90% of children with detectable viral loads. We found few children achieved virologic suppression after failure was detected but the odds of virologic suppression were significantly higher for children on a PI-based versus NNRTI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In Mali, baseline NNRTI resistance was common in children without reported PMTCT drug exposure and was associated with increased risk of treatment failure [ 33 ]. Reports from Central African Republic [ 35 ] and Kenya [ 34 ] show drug resistance in as high as 90% of children with detectable viral loads. We found few children achieved virologic suppression after failure was detected but the odds of virologic suppression were significantly higher for children on a PI-based versus NNRTI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines provide for drug resistance testing, a vital component in management of treatment failure (52) and subsequently prevents pragmatic drug switches that could lead to drug resistance. Studies have reported that upto 60-90% children who don’t attain viral suppression tend to have drug resistance (53) (54), especially mutations to PI drugs which may hinder success of HIV care interventions in children. In this study amongst the CYALHIV who had been switched from PI to DTG based regimen as a result of non-suppression, only 33% had received drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal drug resistance can result from either maternal exposure to nevirapine 18 or after neonatal administration. 18,19 Preparation of the infant raltegravir formulation is difficult, and raltegravir has a complex dosing regimen with multiple changes in dose and frequency within the first 2 months of life to avoid high exposures and potential toxicity. 6 Lopinavir/ritonavir and dolutegravir have been shown to be safe and efficacious when used in combination regimens in older infants, but reports of neonatal toxicity and/or lack of formulations with adequate neonatal pharmacokinetic and safety data 20 restrict their use to infants over 2 21 and 4 weeks 22 of postnatal age, respectively.…”
Section: Discussionmentioning
confidence: 99%